Specifying the Effect of Social Welfare Expenditures on Homicide and Suicide: A Cross-National, Longitudinal Examination of the Stream Analogy of Lethal Violence. (2nd January 2018) - Tuttle, James
Abstract : This study is an extension and cross-national test of the Stream Analogy of Lethal Violence (SALV). The SALV is an integrated theory of homicide and suicide that hypothesizes a relationship between "socially patterned" sources of frustration and lethal violence. By drawing on the insights of General Strain Theory and Institutional Anomie Theory, this study extends the SALV by assessing the impact of "decommodification" on the lethal violence rate. Partial support is found for this modified version of the SALV, as lagged measures of social expenditures are negatively associated with total lethal violence. The findings of this study suggest that social welfare expenditures in OECD nations protect citizens from lethal violence while austerity measures may contribute to greater rates of violent death.